Factors Affecting Sources of Information Utilization - Mandal , B.K.; De , Dipak (Indian Journal of Extension Education, 2013)
An attempt has been made to study the factors affecting information sources utilization by the farmers. The study was  conducted with a sample of 300 farmers drawn randomly from Banka and Rajaun blocks of Banka district of Bihar. The  study revealed that socio-economic status, interpersonal interaction, and value orientation were the main factors  determining the sources of information utilized by farmers. The value of co-rrelation coefficient (r = 0.566) was found to  be highest in case of socio-economic status, whereas the regression co-efficient was found to be highest (b=0.328) in case  of interpersonal interaction.
Keywords: Source; information; utilization; socio-economic status; interaction; value